2022
DOI: 10.33448/rsd-v11i8.30394
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological evaluation of stethoscopes used in the clinical routine of Veterinarians in the Metropolitan Region of Recife, Pernambuco, Brazil

Abstract: We evaluated the level of contamination of stethoscopes used in the clinical routine of veterinarians. Specimens from 15 stethoscopes were cultured and analyzed before (M0) and after (M1) disinfecting the stethoscope diaphragm with alcohol at 70ºGL. At moment M0, bacterial growth was observed in 73.33% (11/15) of the stethoscopes. Seventeen strains were isolated, and the majority (41.2%, 7/17) were Bacillus spp. followed by Staphylococcus spp. (35.3%, 6/17) and Micrococcus spp. (23.5%, 4/17). In samples collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Unlike most studies that primarily investigate stethoscopes used by human physicians, our research with Souza et al, Leite et al, and Fujita et al's study specifically examined stethoscopes employed in veterinary settings (Fujita et al, 2013;Leite et al, 2023;Souza et al, 2022). In the study by Souza, bacterial growth was observed in 73.33% of stethoscopes before disinfection, and Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Unlike most studies that primarily investigate stethoscopes used by human physicians, our research with Souza et al, Leite et al, and Fujita et al's study specifically examined stethoscopes employed in veterinary settings (Fujita et al, 2013;Leite et al, 2023;Souza et al, 2022). In the study by Souza, bacterial growth was observed in 73.33% of stethoscopes before disinfection, and Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 96%
“…In the study by Souza, bacterial growth was observed in 73.33% of stethoscopes before disinfection, and Staphylococcus spp. accounted for 35.3% of the isolates (Souza et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation